AlGaAs anode heterojunction PIN diodes. Issue 5 (27th March 2013) - Boles, T.; Brogle, J.; Hoag, D.; Carlson, D.; Krishna, Sanjay; Plis, Elena
Abstract This paper describes the development of a heterojunction AlGaAs/GaAs PIN diode as a revolutionary improvement as compared to the homojunction GaAs PIN diode commonly used in microwave systems for commercial and military applications. In a heterojunction device the injected carriers from the junction are confined by the bandgap discontinuity between the AlGaAs/GaAs layers. This confinement effectively reduces the series resistance within the I‐region of a PIN diode. Simulations of both single and double heterojunction PIN diodes predict a significant improvement in the return loss and insertion loss as compared to an equivalent GaAs PIN structure. In particular, the single heterojunction PIN diode, when simulated at a bias of 10 mA, indicates a factor of two reduction in high frequency insertion loss. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)